Population structure of Phytophthora infestans collected from potatoes in Guatemala and Honduras - Izarra, M.; Pérez, W.; Vasquez, E.; Perez, G.; Gamboa, S.; Andrade-Piedra, J.L.; Montejo, L.; Sanders, A.; Kreuze, Jan F. (2025)
Late blight caused by Phytophthora infestans poses a significant global threat to potato and tomato cultivation with profound historical and ongoing impacts on food security. In Central America, particularly in Guatemala and Honduras, the disease has intensified over the last decade, possibly due to favorable climatic conditions and changes in local pathogen populations.